The purest bond : understanding the human-canine connection - Golbeck, Jen; Colino, Stacey (Atria Books, an imprint of Simon & Schuster, Inc., 2023)
"Dogs have been considered people's best friend for thousands of years, but never has the relationship between humans and their canine companions been as vitally important as it is today. With all of the seismic shifts in today's world, rates of anxiety and depression have been skyrocketing, and people have been turning to their dogs for solace and stability. Amidst these dire realities, something wonderful has taken shape. In the United States alone, dog adoptions doubled during the COVID-19 pandemic. As people have brought furry friends into their lives for the first time or seized this opportunity to deepen the connections they already have, they are looking to understand how owning a dog can change their lives. Now, The Purest Bond explores the benefits our dogs can have on our physical, emotional, cognitive, and social well-being, often without our realizing it. Weaving together groundbreaking research and touching real-life stories, The Purest Bond explores not just the social benefits of owning a dog but the science of how dogs improve our emotional and physical health, mental acuity, and our ability to focus and absorb information. Most importantly, they remind us of what's right in the world-love, trust, affection, playtime, fresh air, and sunshine-even when so much feels wrong"--